Globalization, communications and Caribbean identity - Dunn, Hopeton S. ed. (Ian Randle Pub. KingstonJM, 1995)
Examines the advantages as well as the deficiencies of technical innovations in the sphere of global communications and the implication of these developments for cultural identity and political sovereignty. Presents case studies from Jamaica, Trinidad and Tobago, Barbados and Canada and analyses the issue of audiences and imported media content. Addresses the important regulatory and ethical issues in the debate on communications and globalization.